(3GdTaGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3ef Gdaf GdKGdK YTQ ef GdLedI GdQGHYI ai GdEdgjGJ s
(3BNQgG (B:s
(3Ydi eKGd cQGgjI HYV GdeQVi ddWYe GdMdh s
(3GfXQ GdLedI GdQGHYI aj GdadSaI GdChdi Qbe (B" 73" (3adSaIs
(3Hg fXGe GdJYbjHIs
(3cJHJ Chd hQbg HNW chais
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdadSaI hGdefWbs